Premio Nacional Anual de Pintura Contemporanea Juan Francisco Elso. - Palacio de Bellas Artes, La Habana; Castano, Enrique; Oria, Lucy Villegas; de Juan, Dra. Adelaida (La Habana : Museo Nacional de la Habana, 1995)
Castellon, Juan Francisco Elso . Pedro Reinaldo Alvarez ; Guisado, Miguel Angel Batista ; Baylac, Nelson Abel Branly ; Camejo, Luis Enrique ; Obaya, Sandra Amelia Ceballos ; Cabrera, Israel Delmonte ; Durruthy, Juan Roberto Diago ; Alvarez, Sara Diaz ; Rodriguez, Lanner Diaz ; Fong, Li Dominguez ; Fong, Liang Dominguez ; Carasa, Carlos Alberto Estevez ; de Zayas, Carlos Estrada ; Llaguno, Vladimir de Leon ; Prego, Tomas Ernesto Maceiras ; Contreras, Renelio Marin ; Valdes, José Marques ; Carracedo, Jorge Luis Miranda ; Padron, Raul René Montero ; Benitez, RAul Perdomo ; Castro, Douglas Darneis Perez ; Lezcano, Maydelina Perez ; Santamarina, Ariel Ramos ; Ricardo, Luis Joaquin Rodriguzez ; Rojas, Cedey de Jesus ; Perez, Joel Humberto Rojas ; Coto, Gabriel Roman ; Guerra, Luis Enrique Silvestre ; Gonzalez, Ezequiel Suarez ; Gonzalez, Raymin Velez ; Perez, Omar Torres ; Toirac Batista, José Angel ; Torrientes, Miguel Sordo ; Vincench, José Angel ; Ortiz, Zenen Vizcaino
biografie
Premio Nacional Anual de Pintura Contemporanea Juan Francisco Elso, Palacio de Bellas Artes, La Habana, junio 1995
Spaans
boek